Examining Innovative Treatment Approaches for Chronic Kidney Disease: A Comprehensive Analysis from the Lens of Pharmacist (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chronic kidney disease (CKD) poses a substantial public health challenge due to its considerable impact on both morbidity and mortality. Around 850 million people across globe are affected by kidney diseases. Effectively managing CKD and its accompanying comorbidities necessitates a multidisciplinary approach, wherein clinical pharmacists assume a pivotal role in enhancing patient care The increasing prevalence of patients grappling with intricate chronic conditions poses a pressing dilemma within global healthcare. Existing care delivery frameworks are strained, finding it difficult to effectively oversee and manage the intricate requirements of this expanding patient demographic. Pharmacist-led interventions have demonstrated a critical role in enhancing medication adherence and addressing drug-related issues among CKD patients. Through a multidisciplinary approach, involving clinical pharmacists, therapy optimization is achieved by identifying and resolving concerns regarding treatment efficacy, safety, and dosage appropriateness. Research indicates a high acceptance rate of pharmacist recommendations by physicians, exceeding 90%, resulting in notable clinical advantages for individuals with CKD. Furthermore, pharmacists can educate patients on the importance of avoiding nephrotoxic medications and supplements, as well as provide guidance on appropriate dose adjustments based on renal function. This paper propose the concept of by working closely with the healthcare team, and then improve guideline adherence and increase the use of evidence-based therapies, ultimately leading to better outcomes for CKD patients. The paper also proposes the integration of clinical pharmacy services into the management of CKD Pharmacists play a vital role in implementing innovative treatment approaches, optimizing medication regimens, and empowering patients to actively participate in their care, thereby improving the overall quality of life for individuals living with chronic kidney disease.